Predictive Value of Combination of D-dimer and Fibrinogen in Diagnosing Acute CVST. Issue 3 (July 2021) - Pathak, Abhishek; Singh, Varun Kumar; Kumar, Anand; Mishra, Vijaya Nath; Joshi, Deepika; Chaurasia, Rameshwar Nath
Background: Cerebral venous sinus thrombosis (CVST) is an uncommon subtype of stroke, and the role of D-dimer and fibrinogen in early diagnosis of CVST has been studied with varying results. The present study aims to study the role of the combination of D-dimer and fibrinogen in early diagnosis of acute CVST. Methods: Forty consecutive confirmed acute CVST cases admitted at a tertiary care center were recruited for the study. D-dimer and fibrinogen were assessed by a rapid semiquantitative latex agglutination assay. Results: Out of the 40 CVST patients, 21 (52.50%) were females. The mean age of the patients was 37.58 years ± 19.17 years. Common clinical features were headache ( N = 38 [95%]), papilloedema ( N = 15 [37.5%]), and seizures ( N = 12 [30%]). Although the sensitivity (75%) of the combination of D-dimer and fibrinogen assay was lower than that of D-dimer or fibrinogen alone, the specificity and positive predictive value (75% each) was higher. Conclusion: The combination of D-dimer and fibrinogen testing may aid in an early diagnosis of acute CVST and in better management.